Uji Sitotoksisitas Ekstak Metanol Jamur Dari Isolat Tanah Di Daerah Istimewa Yogyakarta Terhadap Sel Kanker Payudara MCF7 - Rosita, Safira Sarah; , Azis Saifudin, Ph.D., Apt (2017)
Soil is a media of growth and development the variety of microorganism. This study aim to explore the fungal of five soil samples in the different ecosystem such as coast, salak plantation, volcano slope, fields, and disposal of cow wasting against the cytotoxic effects of breast MCF 7 cancer cell line. Soil sample was cultured and growing of fungal identified macroscopically. The extraction of fungal sample and Czapek dox media used methanol. Cytotoxic test with MTT assay method was done against breast MCF 7 cancer cell line with variants sample concentration 500; 250; 125; 62,5; 31,25 μg/mL. Qualitative test was carried out on samples that have IC50 with stationary phase silica plate GF254 and mobile phase n-hexane : ethyl acetate (1:3). The result of cytotoxic test showed extract methanol of fungal coast had IC50 values 140 μg/mL, the other four extract methanol of fungal increased cell live in MCF 7 cell line. Qualitative test was carried out on extract methanol of fungal coast, showed the separation of components that were not owned Czapek dox media. So that inferential the extract methanol of fungal coast has an inhibitory effect on the growth of MCF 7 cells, the other four extract methanol of fungal has no cytotoxic effects on MCF 7 cells. Qualitative test is known that extract methanol of fungal coast has varying component.